An Unaligned Alliance: Thailand‐U.S. Relations in the Early 21st Century. Issue 1 (16th January 2016) - Pongsudhirak, Thitinan
Abstract : U.S.‐Thai security relations are "underperforming" due to major shifts in Thailand's and the United States' relations at the interactive domestic, regional, and international levels. The recent predominance of the military in Thailand's domestic politics has clashed with Washington's interpretation of the Shinawatra family's prior ascent to power through electoral processes. China's rise and its efforts to court the current Thai government by staying out of Thailand's internal politics has further exacerbated tensions with American policymakers who had already reduced the scope and depth of ties with Bangkok. How Thailand's political polarization is resolved will be most consequential to the future of Thai‐U.S. security relations. However, continued U.S. alliance relations remain essential for Thailand in view of China's intense campaign to woo Thailand's coup leaderships in 2006 and 2014. A lopsided Thai‐Chinese relationship puts at risk Thailand's traditionally masterful and clever foreign policy pragmatism and undercuts the traditional benefits that both the United States and Thailand have derived from their longstanding alliance relationship.